2012
DOI: 10.2106/jbjs.k.00406
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Physical and Social Functioning, and Quality of Life in Individuals with Multiple Hereditary Exostoses in the Netherlands

Abstract: Background: This study aimed to assess pain and quality of life in a large cohort of patients with multiple hereditary exostoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 16 publications
7
71
1
11
Order By: Relevance
“…Pedrini et al [11] did not specify the age of their cohort but proposed a classification scheme based on skeletal deformity and functional limitation that included patients in childhood, preadolescence, adolescence, and skeletal maturity. Goud et al [4] reported a cohort with a median age of 29.1 years (range, 1-80 years) that closely mirrors the median age of respondents in our study, which is 28.7 years (range, \ 1-85 years).Thus we believe our survey population is a worthy cross section of patients with multiple hereditary exostoses. Goud et al [4] reported that beyond the effects of pain, multiple hereditary exostoses often causes limitations in patient employment, physical activities (especially sports), and activities of daily living, thereby more comprehensively quantifying the burden of disease.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Pedrini et al [11] did not specify the age of their cohort but proposed a classification scheme based on skeletal deformity and functional limitation that included patients in childhood, preadolescence, adolescence, and skeletal maturity. Goud et al [4] reported a cohort with a median age of 29.1 years (range, 1-80 years) that closely mirrors the median age of respondents in our study, which is 28.7 years (range, \ 1-85 years).Thus we believe our survey population is a worthy cross section of patients with multiple hereditary exostoses. Goud et al [4] reported that beyond the effects of pain, multiple hereditary exostoses often causes limitations in patient employment, physical activities (especially sports), and activities of daily living, thereby more comprehensively quantifying the burden of disease.…”
Section: Discussionsupporting
confidence: 76%
“…Pedrini et al [11] had a study population that consisted of 50.7% males and 49.3% females while Goud et al [4] had a study population of 45% males and 55% females [4,11]. Our study population included 56% females and 44% males.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations